2010
DOI: 10.4067/s0718-22442010000200010
|View full text |Cite
|
Sign up to set email alerts
|

Los Restos Óseos Humanos De La Colección De La Misión Salesiana "La Candelaria" (Río Grande, Argentina)

Abstract: RESUMENLa colección de restos óseos humanos del Museo de la antigua Misión Salesiana de Río Grande, como otras colecciones de Patagonia Austral, es en parte el resultado de donaciones y recuperaciones realizadas por aficionados y personal del museo en diferentes épocas. Estos materiales generan información sobre la variedad de situaciones que se presentan en la región, independientemente de que sus conjuntos no puedan ser asociados en la mayoría de los casos a un sitio en particular. Dentro de este marco, el o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
3
1
2
Order By: Relevance
“…From the sample studied in this paper, a higher prevalence of porotic hyperostosis rather than cribra orbitalia has been recorded, following the same tendencies previously reported in Tierra del Fuego (Pérez-Pérez and Lalueza-Fox, 1992;Guichón, 1994;Schinder and Guichón, 2003;Suby and Guichón, 2010). The higher frequency of vault lesions over orbital lesions is in general contrary to the results informed in other ancient populations, in which cribra orbitalia was more prevalent (e.g.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…From the sample studied in this paper, a higher prevalence of porotic hyperostosis rather than cribra orbitalia has been recorded, following the same tendencies previously reported in Tierra del Fuego (Pérez-Pérez and Lalueza-Fox, 1992;Guichón, 1994;Schinder and Guichón, 2003;Suby and Guichón, 2010). The higher frequency of vault lesions over orbital lesions is in general contrary to the results informed in other ancient populations, in which cribra orbitalia was more prevalent (e.g.…”
Section: Discussioncontrasting
confidence: 51%
“…Walker, 1986;Grauer, 1993;Lovell, 1997;Wright and Chew, 1998;Piontek and Kozlowsky, 2002;Keita, 2003;Facchini et al, 2004;Blom et al, 2005;Keenleyside and Panayotova, 2006), the impact and causes of anemia in populations from southern Patagonia have been little documented. During the last decade of the 20th century, several studies reported a high frequency of porotic hyperostosis and a low frequency of cribra orbitalia in populations from Tierra del Fuego (Pérez-Pérez and Lalueza Fox, 1992;Guichón, 1994;Schinder and Guichón, 2003;Suby and Guichón, 2010). However, the archaeologically decontextualized condition of most of the study samples, commonly lacking spatial and paleodietary information, limited the data interpretations, while no studies from the continental extreme of southern Patagonia are currently available.…”
Section: Introductionmentioning
confidence: 99%
“…In Tierra del Fuego, Suby and others (2008) identified three circular traumatic lesions without new bone formation in the skull of a skeleton recovered from the Puesto Pescador 1 site (Atlantic coast of Tierra del Fuego), dated to 335 ± 35 years BP; these lesions were attributed to a violent episode. Finally, Suby and Guichón (2010) reported two cases of interpersonal violence in remains of the skeletal commingled collection housed in the Salesian Mission La Candelaria (Rio Grande, Tierra del Fuego). One of them is an adult male pelvis with two lithic projectile fragments encrusted in both iliac bones, one of which probably compromised the abdominal organs.…”
Section: Recent Paleopathological Researchesmentioning
confidence: 99%
“…ISSN-e 1850-373X poblaciones de la región del noroeste argentino (e.g., Gheggi, 2014;Seldes y Botta, 2014), Sierras Centrales (Fabra et al, 2015), Pampa (Berón, 2014), transición pampeano-patagónica oriental (e.g., Flensborg, 2011) y norte de Patagonia (Barrientos y Gordón, 2004;Gordón, 2015). Por el contrario, en Patagonia austral (PA), las investigaciones se han centrado en descripciones de lesiones traumáticas en estudios de caso o intrasitio (e.g., L'Heureux y Amorosi, 2009; Suby et al 2009;Suby y Guichón, 2010), con excepciones, como pueden ser los realizados en grandes muestras, por ejemplo, el publicado recientemente por Flensborg y Suby (2020).…”
unclassified